Membangun Aplikasi Chatbot Berbasis Web Pada CV. Unomax Indonesia - Wijaya, Teddy; Rusli, Muhammad; Syah Rany, Erwin; Fryonanda, Harfebi (KALBISCIENTIA Jurnal Sains dan Teknologi, 2019)
The development of Internet technology is widely used for positive things in helping human work, one of which facilitates communication between humans. In this case, CV. Unomax Indonesia is still relying on human as an online customer service to respond to inquiries from customers. As customers grow, it is less effective for customers who want to get quick reply information without time constraints. This study aims to create a web-based information system in the form of chatbot application that can be used by CV. Unomax Indonesia to respond to customer inquiries quickly. The method used is the prototype method as a modeling tool. This application uses PHP programming language and MySQL database. The result of the built chatbot application is based on test results using black box testing, it can be concluded that this application can run well and answer each question quickly as expected.